Light Metal Alloys Applications - Monteiro, Waldemar A. (IntechOpen, 2014)
Lightweight alloys have become of great importance in engineering for construction of transportation equipment. At present, the metals that serve as the base of the principal light alloys are aluminum and magnesium. One of the most important lightweight alloys are the aluminum alloys in use for several applications (structural components wrought aluminum alloys, parts and plates). However, some casting parts that have low cost of production play important role in aircraft parts. Magnesium and its alloys are among the lightest of all metals and the sixth most abundant metal on earth. Magnesium is ductile and the most machinable of all metals. Many of these light weight alloys have appropriately high strength to warrant their use for structural purposes, and as a result of their use, the total weight of transportation equipment has been considerably decreased.